Representasi Gejala Overthinking dalam Iklan GoFood Kajian Semiotika Visual Roland Barthes - Syarifa Luthfatus; Kunarsih Mely; Rifqi Nadya Fatikhul; Gladi Pawestri Utami (Jurnal Riset Rumpun Seni, Desain dan Media, 2024)
The term overthinking has become part of the everyday vocabulary among Generation Z, reflecting a tendency toward excessive deliberation in ordinary situations, including choosing food. The “Overthinking” advertisement by GoFood presents a compelling visual representation of this dilemma through metaphorical symbols such as a talking forehead, piles of clocks, and zodiac characters that construct a complex visual narrative of indecision. This study aims to examine how symptoms of overthinking are visually represented in the advertisement using Roland Barthes’ semiotic approach. The research employed a qualitative method, utilizing observation and documentation techniques to analyze visual structures across scenes. The findings reveal that the advertisement conveys its message through denotative, connotative, and myth-based signs, illustrating how Generation Z interprets the burden of choice in a digital cultural context. The results demonstrate how visual communication strategies can foster empathy while offering solutions to the everyday anxieties of a young audience. This study contributes to the development of visual semiotics discourse in the field of visual communication design and offers insights for advertising practices grounded in social issues.